Guidelines on eosinophilic esophagitis: evidence‐based statements and recommendations for diagnosis and management in children and adults. Issue 3 (1st April 2017) - Lucendo, Alfredo J; Molina‐Infante, Javier; Arias, Ángel; von Arnim, Ulrike; Bredenoord, Albert J; Bussmann, Christian; Amil Dias, Jorge; Bove, Mogens; González‐Cervera, Jesús; Larsson, Helen; Miehlke, Stephan; Papadopoulou, Alexandra; et al.
Abstract : Introduction: Eosinophilic esophagitis (EoE) is one of the most prevalent esophageal diseases and the leading cause of dysphagia and food impaction in children and young adults. This underlines the importance of optimizing diagnosys and treatment of the condition, especially after the increasing amount of knowledge on EoE recently published. Therefore, the UEG, EAACI ESPGHAN, and EUREOS deemed it necessary to update the current guidelines regarding conceptual and epidemiological aspects, diagnosis, and treatment of EoE. Methods: General methodology according to the Appraisal of Guidelines for Research and Evaluation (AGREE) II and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was used in order to comply with current standards of evidence assessment in formulation of recommendations. An extensive literature search was conducted up to August 2015 and periodically updated. The working group consisted of gastroenterologists, allergists, pediatricians, otolaryngologists, pathologists, and epidemiologists. Systematic evidence‐based reviews were performed based upon relevant clinical questions with respect to patient‐important outcomes. Results: The guidelines include updated concept of EoE, evaluated information on disease epidemiology, risk factors, associated conditions, and natural history of EoE in children and adults. Diagnostic conditions and criteria, the yield of diagnostic and disease monitoring procedures, and evidence‐based statements and recommendation on the utility of the several treatment options for patients EoE are provided. Recommendations on how to choose and implement treatment and long‐term management are provided based on expert opinion and best clinical practice. Conclusion: Evidence‐based recommendations for EoE diagnosis, treatment modalities, and patients' follow up are proposed in the guideline.